Triggering Factors for (Self-)Reflection. An Inquiry in the Context of an ePortfolio Initiative - Gernot Dreisiebner; Peter Slepcevic-Zach; Michaela Stock (Forum Neue Medien in der Lehre Austria, 2021)
The purpose of this paper is to give insight into an ongoing ePorfolio (ePF) implementation for students of a five semester Master's Programme for Business Education and Development. An accompanying study of this ePF implementation aims at evaluating the students' self-perception of their competence development. At six points of time throughout their Master's Programme, students fill in questionnaires totalling up to 2,326 questionnaires by March 2020. The focus of this paper lies on the triggering factors for (self-)reflection. The results show, that obligation is a main triggering factor for (self-)reflection, thus indicating the importance of curricular integration of the ePF work for a successful (self-)reflection process.